Vacinação contra papilomavírus humano e outros patógenos: registros e percepções de jovens universitários em município da Amazônia brasileira - SILVEIRA, Renan Luis Cardoso da (2023)
This study recorded HPV vaccination coverage and the perceptions of young university students regarding vaccination against HPV and other pathogens. Materials and methods: This descriptive and exploratory study, with a qualitative approach, was developed with 20 university students enrolled in degree courses (UL) in the municipality of Bragança, Pará, from June to July 2022. Using a digital form, UL provided sociodemographic and academic information, about vaccination against HPV and other pathogens, and their perceptions about barriers and the facilities for talking about vaccination. Most participants were young, female, declared themselves single and in the final stages of the course. Everyone stated that they were aware of HPV infection and its vaccine, but only 50% of them received two doses of this vaccine during adolescence. Family guidance was the main reason for failure in the HPV vaccination schedule. Fear about vaccines and the sharing of fake news make it difficult to talk about vaccination in the school environment and in the community. On the other hand, efficiency and protection against pathogens can facilitate the conversation and encouragement for vaccination. Still, many UL said they have family members who do not receive the flu vaccine annually or have not yet completed the flu and COVID-19 vaccination schedule. This study detected low HPV vaccination coverage among young university students and reinforced the importance of strengthening health promotion in the population.